Pengaruh Kualitas Produk Dan Green Marketing Terhadap Keputusan Pembelian NPURE Melalui Online Customer Review Sebagai Variabel Intervening (Studi pada Generasi Z Pemakai Produk NPURE di Kota Malang). - Salsabilla, Salma; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to analyze the Influence of Product Quality and Green Marketing on NPURE Purchasing Decisions with Online Customer Reviews as an intervening variable. This study is based on the increasing awareness of Generation Z towards environmentally friendly products and the influence of Online Reviews on purchasing decisions. This study uses a quantitative method with an explanatory research approach. Data were collected through questionnaires from 100 Generation Z respondents in Malang City who had used NPURE products for at least three months. Data analysis was carried out using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that product quality and Green Marketing had a significant effect on Online Customer Reviews and purchasing decisions. Online Customer Reviews were also proven to be a mediating variable that strengthened the relationship between product quality, Green Marketing, and purchasing decisions. This study emphasizes the importance of improving product quality, implementing effective Green Marketing strategies, and managing Customer Reviews to improve consumer purchasing decisions. Keywords: Product Quality, Green Marketing, Online Customer Reviews, Purchasing Decisions, Generation Z, NPURE.